The Long Road to Health and Prosperity, Southern Sweden, 1765-2015. Research Contributions From the Scanian Economic-Demographic Database (SEDD) - Tommy Bengtsson; Martin Dribe (Historical Life Course Studies, 2021)
The Scanian Economic-Demographic Database (SEDD) at the Centre for Economic Demography (CED), Lund University was built to answer questions derived from previous research using macro data from 1749 onwards. It includes longitudinal micro data for a regional sample of rural, semi-urban, and urban parishes in southern Sweden from 1646 to 1968 for approximately 175,000 individuals. In addition to the data on births, deaths, marriages, and occupations, it includes data on migration, household size, landholdings, taxation, and heights from the 1800s onwards and on income from 1865 onwards. After being linked from 1968 to 2015 to a range of national registers with detailed demographic and socioeconomic information, it includes 825,000 individuals. The richness and wide range of micro data have allowed researchers to follow individuals throughout their lives and across generations, covering extensive periods, and to make comparisons with results from macro data. This research has partly confirmed the established view on long-term changes in living standards and demographics in Sweden but has also brought into question some previously held truths.